(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Solid waste management (SWM) is one of the biggest issues worldwide due to the rapid urbanization and population increases. Awareness and participation to SWM should start at home. Engaging students to SWM even in the midst of distance learning during pandemic can help reduce environmental harm. Thus, this study was conducted to determine the level of awareness and participation towards SWM among respondents. The researchers used descriptive correlational research design to gather data from 138 Junior High School students enrolled at Union Christian College using a survey questionnaire. Weighted mean was used to describe the awareness and participation to SWM, while Pearson Product Moment Correlation was used to determine the significant relationship between the variables. The findings show that the students have good grasp of knowledge in the basic concept of solid waste, improper disposal, prohibited activities, school initiative of SWM, importance of solid waste management, roles and responsibilities as a student and sources of information toward SWM. Most notably, they are highly aware of its importance. However, students have a lack of knowledge regarding to the laws and ordinances related to SWM. The findings also indicate that the students know how to properly segregate, reduce, reuse, recycle, and dispose of waste. While the findings indicate that they know and practice SWM, there is a need to enhance these and to make them at optimal level. Furthermore, there is a strong positive significant relationship between their knowledge and practice which means that the more they know about SWM, the more they will practice it. The findings imply that the respondents are aware of SWM leading to its practice. To improve these areas, the researchers recommend the adoption of a home-based segregation plan is to further enhance the awareness and the participation of the respondents to SWM.